Flax Issue in Latgale in the 1920s - Malahovskis, Vladislavs (Acta humanitarica academiae Saulensis, 2019)
The issue of flax was topical both in Latgale region and in Latvia in the 1920s. Flax fibre and linseeds were very important export goods in Latvia. Latgale region was the main producer of flax in the country, thanks to which Latgalian small holders could get real income. More than 10% of all agricultural land was used to grow flax. However, small  holders did not get real income due to the establishment of a national flax monopoly, when flax was sold at the cheapest price. As the price of flax was very changeable on the world market, it was stored in warehouses and sold when the price grew. As a result, flax growers received only about a tenth of the profits the country got for flax exports. The government policy for getting too much profit from flax exports was criticized by Latgalian politicians. They defended the interests of flax growers. The market of flax in Latgale as well as in Latvia was also discredited by certain illegal practices of flax producers and collectors for self-benefit.
Keywords: Latgale; flax; monopoly; Latgalian politicians